Standard Evaluation of Damage to Critical Lands in Medium Plains in Pasuruan Regency - Maroeto; Rossyda Priyadarshini; Wahyu Santoso (Nusantara Science and Technology Proceedings, 2021)
Critical land is land that is currently not or less productive in terms of agricultural use, because its management and use does not or does not pay attention to soil conservation principles. Based on the level of physical damage to the soil, critical land is land that has lost the fertile top soil due to erosion, so that the land becomes unproductive. The procedure for measuring land damage due to human actions in agricultural, plantation, forestry, and city park areas has been regulated in the Minister of Environment Regulation No. 07 of 2006. In Government Regulation no. 150 of 2000, the control of terrestrial environmental damage can be grouped into a preventive approach and a reactive approach. The purpose of this research is to identify the criticality level in terms of the Damage Standard in the Medium Plain, Pasuruan Regency comprehensively and interrelated. This type of research is a survey research, the research focuses on identifying in terms of the Damage Standard, the location in this study is deliberately (purposive area sampling) set. in the medium-land area of ??Pasuruan Regency which was identified as critical land with a total area of ??1,949.79 Ha covering two areas, namely Purwodadi and Purwosari Districts. The two areas have 3 land use units including plantation agricultural activities, rainfed rice fields, and dry fields in Pasuruan Regency, the measurement guideline is based on the PERMEN LH guideline No. 07 of 2006 measuring the level of soil damage for biomass products. The conclusions obtained 1. Medium plains based on the results of the Interrelation of Critical Land Evaluation Parameters on the Distribution of Agricultural Land, the biophysical limiting factor that is the main obstacle so that land degradation occurs and land use that is not in accordance with its designation on mediumland agricultural land. 2. Land that meets the critical criteria according to observations shows that it reduces the quality of land for moderate damage, has problems with surface rock, degree of water release, redox and the number of microbes (bacteria) as a result of intensive processing. 3. Land conservation efforts are an alternative option in land management, reducing the use of inorganic pesticides and fungicides, making irrigation and drainage channels to avoid water saturation, giving organic fertilizers and selecting plants according to land characteristics so that water availability and land productivity can be increased.